Long-Term Improvements in Chronic Axial Low Back Pain Patients Without Previous Spinal Surgery: A Cohort Analysis of 10-kHz High-Frequency Spinal Cord Stimulation over 36 Months. Issue 6 (24th October 2017) - Al-Kaisy, Adnan; Palmisani, Stefano; Smith, Thomas E; Carganillo, Roy; Houghton, Russell; Pang, David; Burgoyne, William; Lam, Khai; Lucas, Jonathan
Abstract: Objective: This prospective, open-label study was designed to evaluate the long-term effectiveness of 10-kHz high-frequency spinal cord stimulation (SCS) in the treatment of chronic axial low back pain with no history of spinal surgery. Methods: Patients with chronic low back pain without previous spinal surgery underwent assessment by a multidisciplinary pain and surgical team to confirm eligibility. After a successful temporary trial of 10-kHz HF-SCS therapy, defined by ≥50% back pain reduction, enrolled subjects underwent permanent system implantation and were followed up for 36 months. Outcome measures consisted of a 100-mm visual analog scale (VAS) for pain intensity, the Oswestry Disability Index (ODI), and a standard measure of health-related quality of life. Results: Twenty-one patients satisfied the inclusion/exclusion criteria. Following a temporary trial, 20 of 21 (95%) subjects were implanted with a pulse generator, and 17 of 20 reached the 36-month time point. From baseline to 36 months, the average VAS pain intensity decreased from 79 ± 12 mm to 10 ± 12 mm, the average ODI score decreased from 53 ± 13 to 19.8 ± 13, and use of opioids decreased from 18 subjects to two subjects. One subject was deceased, unrelated to the study, one subject was explanted due to loss of effectiveness, and one subject was lost to follow-up. Conclusions: These results suggest that 10-kHz high-frequency SCS may provide significant, long-term back pain relief, improvement in disability and quality of life, and reduction in opioids for nonsurgical refractory back pain.